High‐Quality Stereo Depth Map Generation Using Infrared Pattern Projection - Jeong, Jae‐chan; Shin, Hochul; Chang, Jiho; Lim, Eul‐Gyun; Choi, Seung Min; Yoon, Kuk‐Jin; Cho, Jae‐il (ETRI journal, 2013)
In this paper, we present a method for obtaining a highquality 3D depth. The advantages of active pattern projection and passive stereo matching are combined and a system is established. A diffractive optical element (DOE) is developed to project the active pattern. Cross guidance (CG) and auto guidance (AG) are proposed to perform the passive stereo matching in a stereo image in which a DOE pattern is projected. When obtaining the image, the CG emits a DOE pattern periodically and consecutively receives the original and pattern images. In addition, stereo matching is performed using these images. The AG projects the DOE pattern continuously. It conducts cost aggregation, and the image is restored through the process of removing the pattern from the pattern image. The ground truth is generated to estimate the optimal parameter among various stereo matching algorithms. Using the ground truth, the optimal parameter is estimated and the cost computation and aggregation algorithm are selected. The depth is calculated and bad‐pixel errors make up 4.45% of the non‐occlusion area.